Study on knowledge level of oil palm smallholder towards the oil palm basal stem rot disease (BSR) - Iqlima, N. I.; Mohammad Amizi, A.; Assis Kamu; Fatimah Kayat; Zul Ariff, A. L. (2015)
Oil Palm industry has been the backbone of Malaysian economy for a number of decades. Approximately 11% present of total land has been cultivated with oil palm. The rapid expansion from 2.03 million hectares of cultivation in 1990 to 5.23 million hectares in 2013 (Malaysian Palm Oil Board, 2014) contributing instability in ecosystem due to monocropping. The oil palm industry not only facing the problems of labour shortage and negatives publicity by the environmentalist but also facing the Basal Stem Rot Disease which caused by the Ganoderma boninense. This paper is to determine the knowledge level of independent and dependent oil palm smallholders due to the oil palm smallholders represent 13.58% or 0.69 million hectares of oil palm industry. This study will identify the knowledge level of the oil palm smallholders whether this group is familiar with Basal Stem Rot Disease. A survey method through face to face interview by using structured questionnaire was used to collect the data from a total 324 respondents among the smallholders in Sabah and Johor. The results indicated most of the smallholders which from the school level education have low level of knowledge pertaining to the Basal Stem Rot Disease (BSR).